Introduction to Creation Music Kumat | Pengantar Musik Kreasi Kumat - I Putu Suardana (GHURNITA: Jurnal Seni Karawitan, 2022)
Kumat's work is a composition of new creations that is packaged with a traditional nuance. This work is an interpretation of the mechanism of bipolar mental disorder compiled through a musical formulation that corresponds to the mechanism of bipolar. This work focuses on two building elements, namely musical formulations and musical nuances, musical formulations are concrete and musical nuances are variable according to the listener's musical experience. Kumat's work uses a modified Jegog gamelan as a medium of expression. The location of the modifications is on the barangan instrumen, kantil, suwir which are made into one stump, with the addition of two other instrumens as melody modifiers, namely kuntung and undir. The process of creating this work is carried out in four stages, namely initial stimulation combined with the concept of Alma M. Hawkins in the book Creating Trough Dance which consists of exploration, improvisation, formation. This work is manifested in the form of creative percussion which is still based on the realm of tradition, the renewal contained in this work lies in the musical formulation that adopts the mathematical science of the magic square as the basis for the formation of the work.